Characterization Of Feti-Oxide Species Occuring In The Ranobe Heavy Mineral Deposit, Madagascar - T. Wallmach (The Southern African Institute of Mining and Metallurgy, 2007)
Heavy mineral deposits are a source of the economic important element titanium, which is contained in minerals such as ilmenite, pseudorutile and rutile. In the Ranobe heavy minerals deposit these minerals occur not only as primary unaltered minerals but also display various degrees of alteration resulting in an increased titanium content of the deposit. The presence of the various FeTi-oxide minerals? textural relations is a reflection of geological processes and may ultimately be used to unravel the geological history of the deposit. These minerals have different chemical and physical properties that influence metallurgical tests and the quality of products produced from various mineral beneficiation streams. It is therefore of metallurgical importance that the minerals are well characterized, defined and monitored during preliminary beneficiation tests.